Decision Support to Improve Railway Track Maintenance in Indonesia: A life Cycle Cost Approach - Rachmad Indrakusuma; Nafilah El Hafizah; Dicky Rahmadiar Aulial Ardi (Jurnal Teknologi dan Manajemen, 2024)
Railway infrastructure is a complex asset and must have a long service life. Therefore, effective maintenance methods are required to achieve optimal results throughout the life cycle. Life Cycle Cost (LCC) is a method of evaluating the total cost associated with the service life of a system and can also be used to determine the most cost-effective method in the long term. This research begins by discussing the failure of major track components such as rails, sleepers and ballast. With the literature study, critical track component degradation models can be developed to identify the causes of failures. Material selection analyses is used to ensure optimal selection in terms of cost and performance. The appropriate type of maintenance is determined to ensure proper and safe operation of the railway track system. The main purpose of this paper is to determine the effective and efficient methods for maintaining railway tracks in Indonesia. In this study, the estimated degradation models of track components are used as the basis for determining component material selection. Existing types of railway maintenance are discussed and involve determining the type of maintenance based on LCC analysis to achieve the most cost-effective method.